PENERAPAN NILAI-NILAI TOTAL QUALITY MANAGEMENT (TQM) DALAM PENGELOLAAN SUMBER DAYA MANUSIA DI MADRASAH - Haryati, Sri (IAIN Ponorogo, 2013)
Generally Madrasah has weak competitiveness in many sectors. One of them is the availability and management of human resources that is less optimal. This has led to the low professionalism of human resources who manage education institutions of Madrasah in Indonesia. As a result, the quality of Madrasah is still left behind by other public educational institutions. Some efforts to achieve a qualified Madrasah especially in terms of availability of professional human resources have been experiencing significant constraints, so that the level of public and government appreciation is relatively less. To improve the performance of Madrasah which is currently underestimated compared to the public schools, it is suggested to implement Total Quality Management (TQM) simultaneously. The application of TQM in Madrasah as Islamic education institution is obviously important to improve and maintain the quality of Madrasah. The implementation of human resource management at Madrasah is very effective in managing the teachers and education staffs in establishing and maintaining the quality of institutions. This is due to the fact that human factor (teacher and education staff) is the most strategic element in the management of Madrasah as Islamic educational institutions.Â Ø±ÙØ Ø§ÙÙ ÙØ§ÙØ³Ø©Â ÙÙ Ø§ÙÙ Ø¯Ø§Ø±Ø³ Ø§ÙØ¯ÙÙÙØ© Ø¹Ø§Ù Ø© Ø¶Ø¹ÙÙØ©. ÙØ§ÙØ³Ø¨Ø¨ ÙÙ Ø°ÙÙ Ø¶Ø¹Ù ÙØ¬ÙØ¯ Ø§ÙÙ ÙØ§Ø±Ø¯ Ø§ÙØ¨Ø´Ø±ÙØ© ØºÙØ± Ø§ÙÙØ¹ÙØ§ÙØ©. ÙØ°Ø§ Ø£Ø¯Ù Ø¥ÙÙ Ø£Ù Ù ÙÙÙØ© Ø§ÙÙ ÙØ§Ø±Ø¯ Ø§ÙØ¨Ø´Ø±ÙØ© Ø§ÙÙ ÙØ¸Ù ÙÙÙ Ø¯Ø§Ø±Ø³ Ø§ÙØ¯ÙÙÙØ© ÙÙ Ø¥ÙØ¯ÙÙÙØ³ÙØ§ â Ø£ØºÙØ¨ÙØ§ â Ø¶Ø¹ÙÙØ©. ÙØ°Ø§ ÙØ¥Ù ÙÙØ¹ÙØ© ÙØ¬ÙØ¯Ø© Ø§ÙÙ ÙØ¸Ù ÙÙ ÙÙÙ Ø¯Ø§Ø±Ø³ Ø§ÙØ¯ÙÙÙØ© Ù ØªØ£Ø®Ø±Ø© Ø¥Ø°Ø§ ÙÙØ±ÙØª Ø¨Ø§ÙÙ ÙØ¸Ù ÙÙ ÙÙÙ Ø¯Ø§Ø±Ø³ Ø§ÙØ¹Ø§Ù Ø©. ÙØ§ÙÙ ØØ§ÙÙØ© ÙØ¥ÙØ¬Ø§Ø¯ Ø§ÙÙ Ø¯Ø§Ø±Ø³ Ø§ÙØ¯ÙÙÙØ© Ø§ÙØ¬ÙØ¯Ø© ÙØ§ ØªØ²Ø§Ù ÙÙÙØ§ Ø¹ÙØ§Ø¦Ù ÙØ«ÙØ±Ø©Ø Ø®Ø§ØµØ© ÙÙÙ Ø§ ÙØªØ¹ÙÙ Ø¨ØªÙÙØ± Ø§ÙÙ ÙØ§Ø±Ø¯ Ø§ÙØ¨Ø´Ø±ÙØ© Ø§ÙÙ ÙÙÙØ© ØØªÙ ÙÙÙÙ Ø§ÙØªÙ Ø§Ù ÙÙØ¨ÙÙ Ø§ÙÙ Ø¬ØªÙ Ø¹ ÙØ§ÙØÙÙÙ Ø©Â Ø¨ÙØ§ ÙØ§ÙØµ. ÙÙØªØ±ÙÙØ© Ø§ÙØ¬Ø§Ø²Ø§Øª Ø§ÙÙ Ø¯Ø§Ø±Ø³ Ø§ÙØ¯ÙÙÙØ© ÙØØ³Ù ØªØ·Ø¨ÙÙ TQM Ù ØªÙØ§ØµÙØ§. ÙÙØ°Ø§ Ø§ÙØªØ·Ø¨ÙÙ â ÙÙ Ø§ÙÙ Ø¯Ø§Ø±Ø³ Ø§ÙØ¯ÙÙÙØ© â Ù ÙÙ Ù Ø¬Ø¯Ø§Ø ÙØ£ÙÙ Ø¨Ù ÙÙ ÙÙ Ø£Ù ØªØ¯Ø§Ø±Ø§ÙÙ Ø¯Ø§Ø±Ø³ Ø§ÙØ¯ÙÙÙØ© Ù ÙÙÙØ§ ÙØªØ±ÙÙØ© Ø¬ÙØ¯ØªÙØ§ ÙØ§ÙÙ ØØ§ÙØ¸Ø© Ø¹ÙÙ ÙØ°Ù Ø§ÙØ¬ÙØ¯Ø©. ÙØªØ·Ø¨ÙÙ Ø¥Ø¯Ø§Ø±Ø© Ø§ÙÙ ÙØ§Ø±Ø¯ Ø§ÙØ¨Ø´Ø±ÙØ© ÙÙ Ø§ÙÙ Ø¯Ø§Ø±Ø³ Ø§ÙØ¯ÙÙÙØ© ÙØ¹Ø§Ù ÙÙ ØªÙØ¸ÙÙ Ø§ÙÙ Ø¯Ø±Ø³ÙÙ ÙØ§ÙÙØ§Ø¦Ù ÙÙ Ø¨Ø§ÙØªØ±Ø¨ÙØ© ÙÙ ØªÙÙÙÙ Ø¬ÙØ¯Ø© Ø§ÙÙ Ø¯Ø§Ø±Ø³ Ø§ÙØ¯ÙÙÙØ© ÙØ§ÙÙ ØØ§ÙØ¸Ø© Ø¹ÙÙÙØ§Ø ÙØ£Ù Ø§ÙØ¹ÙØµØ± Ø§ÙØ¥ÙØ³Ø§ÙÙ ÙÙ Ø¹ÙØµØ± ÙØ§Ù ÙÙ ØªÙØ¸ÙÙ ÙØ¥Ø¯Ø§Ø±Ø© Ø§ÙÙ Ø¤Ø³Ø³Ø© Ø§ÙØªØ±Ø¨ÙÙØ© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© (Ø§ÙÙ Ø¯Ø§Ø±Ø³ Ø§ÙØ¯ÙÙÙØ©) .